PERFORMAN BCS KERBAU LUMPUR DOMPU (Swamp Buffalo) JANTAN DAN BETINA DIBERIKAN PAKAN LIMBAH JAGUNG SECARA EKSTENSIF DI KABUPATEN DOMPU NTB - Husni (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2022)
Buffalo (Bubalus bubalis) is one of the large ruminants that have an important contribution in the development of national livestock. Local buffalo has its own advantages to be developed because it can survive on low-quality feed, is tolerant of tropical parasites and its existence has been integrated with the life of farmers in rural areas. The research has been carried out for 8 months starting from July 16, 2015 to March 16, 2016, with an allocation of 240 days of data collection in the field to determine the BCS performance of male and female mud buffaloes fed corn waste extensively in Dompu Regency, NTB. The observed variable was the performance of BCS Buffalo Mud (Swamp Buffalo) male and female given extensive corn waste feed in Dompu Regency, West Nusa Tenggara. The results showed that in the age group of 7-12 months, there was a significant difference (p<0.05) between BCS of female buffalo in Dompu (4.80±0.45) compared to BCS of female buffalo in Manggelewa (4.10±0.66). However, in the age group 7-12 months, the BCS of male buffalo Doro Ncanga in Manggelewa (4.31±0.66) was greater (p<0.05) than the BCS of buffalo in Kempo (4.19±0.75) and Dompu (3.58±0.76).